2018
DOI: 10.5433/1679-0359.2018v39n1p87
|View full text |Cite
|
Sign up to set email alerts
|

Study of soil physical properties and water infiltration rates in different types of land use

Abstract: Studying the changes in soil properties caused by different land uses allows measures to be adopted that will reduce the risk of future negative effects. The aim of this study was to evaluate soil physical properties and quantify water infiltration for different types of land use in the Santa Catarina Plateau of southern Brazil. The research was conducted on a 1,200 ha rural property. The land use types selected were natural forest (NF), planted pine (PP), crop-livestock integration (CLI), and burned natural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The high porosity could be due to the coarseness of the soil structure hence more pore spaces in the natural forest. This is in line with Santos et al [15] who observed lower bulk densities and higher porosity in the natural forest as compared to the other land use types.…”
Section: Bulk Density and Porositysupporting
confidence: 92%
See 1 more Smart Citation
“…The high porosity could be due to the coarseness of the soil structure hence more pore spaces in the natural forest. This is in line with Santos et al [15] who observed lower bulk densities and higher porosity in the natural forest as compared to the other land use types.…”
Section: Bulk Density and Porositysupporting
confidence: 92%
“…Assessment of the impacts due to land use types on soil hydrologic response at regional scale is difficult due to detailed information on soil properties and land use types that is rarely available [1]. Studying the changes in soil properties caused by different land uses allows measures to be adopted that will reduce the risk of future negative effects [15]. Changes in infiltration capacity and soil water repellency are good parameters and indicators for soil hydrological functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Although the average pressure exerted on the surface layers is less than 2500 KPa, in some places these values reached 4500 KPa, resistance considered high, where in this situation it can present limitations to the development of the root system of the plants, and can be explained by the values of [25].…”
Section: Resultsmentioning
confidence: 99%
“…The largest eigenvectors for infi ltration rate and capacity, macro and microporosity and soil density allow to infer that soil characteristics can be used to explain the equal runoff values (Santos et al, 2018). Except for macroporosity, these soil characteristics did not diff er in the interval of one year between the rehabilitation periods (2.5 and 3.5 years), demonstrating that they demand more time for modifi cation (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 98%